Temporal variations of bomb radiocarbon inventory in the Pacific Ocean - Peng, T. H.; Key, R. M.; Ostlund, H. G. (Marine Chemistry, 1998)
The natural and anthropogenic components of the radiocarbon measurements from seawater samples can be successfully separated by an improved method, which is based on a very well-defined relationship between natural radiocarbon and dissolved silica observed mainly during the GEOSECS survey for waters beneath 1000 m depth. This relationship is further reconfirmed by the C-14 measurements from large volume samples taken in the deep waters in the Pacific Ocean during the recent WOCE survey program. Analysis of upper ocean C-14 measurements made along 152 degrees W, and north of 20 degrees N, in the northeastern Pacific Ocean during the NOAA's CGC91 cruise, which is a part of the WOCE survey program, indicates that the bomb C-14 inventory in this part of the ocean has increased by 22% since the GEOSECS measurements made in 1974, This increase is consistent with the model prediction of 25% for the northern hemisphere ocean. Change of the surface water bomb Delta(14)C values during this period is insignificant, This feature is also consistent with the model simulation. Results of this new analysis will provide useful information of the temporal variations of bomb C-14 inventory in the ocean, in addition to the spatial distribution, which can be used as powerful constraints in calibrating the global ocean carbon cycle models, especially those based on three-dimensional ocean general circulation models, for estimating the uptake of CO2 by the ocean. (C) 1998 Elsevier Science B.V.
Zm128Times Cited:22Cited References Count:18